Cochrane Database of Systematic Reviews 2010
DOI: 10.1002/14651858.cd008403
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive surgery versus open surgery for the treatment of solid abdominal and thoracic neoplasms in children

Abstract: Minimally invasive surgery versus open surgery for the treatment of solid abdominal and thoracic neoplasms in children (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…A recent review of minimally invasive surgery (MIS) vs open surgery (OS) for the treatment of abdominal tumors failed to reach any conclusions regarding antitumor efficacy and surgical morbidity [8].…”
Section: Is Mia Superior To Oa?mentioning
confidence: 99%
“…A recent review of minimally invasive surgery (MIS) vs open surgery (OS) for the treatment of abdominal tumors failed to reach any conclusions regarding antitumor efficacy and surgical morbidity [8].…”
Section: Is Mia Superior To Oa?mentioning
confidence: 99%
“…Most of these studies do not examine long‐term outcomes and few have the power to compare MIS and open techniques for either short‐term surgical or oncologic outcomes or long‐term survival . A recent Cochrane review indicated that there are no randomized or controlled clinical trials that compare MIS to open surgery in pediatric abdominal malignancy . Given the knowledge gap in this area, we compared open and MIS surgery in a retrospective cohort analysis of children with neuroblastoma and WT using a large national cancer registry to define current clinical practices, oncologic outcomes, and long‐term survival.…”
Section: Introductionmentioning
confidence: 99%
“…have shown that laparoscopic resection of solid tumours, such as neuroblastomas, is feasible. [ 6 ] The study by Romano et al . comparing open to laparoscopic adrenalectomy in children but is not randomised.…”
Section: Discussionmentioning
confidence: 99%